A política de Promoção por Mérito na rede de ensino estadual paulista: um processo complexo e multifacetado - Souza, Valéria de (2015)
This work aims to question the current actions of teacher evaluation, specially the policy of Merit-based Promotion, with the objective of analyzing them according to the manifestations of the educational professionals of the Department of Education of the State of São Paulo. The theoretical references include the following authors: Stephen Ball, with his policy cycle approach; Viñao Frago, in order to understand the concept of reform in the perspective of the school culture, the managers culture and the reformers culture; Claude Lessard, to accomplish the analysis of different approaches about teacher evaluation. This research is considered having quantitative and qualitative nature, involving a descriptive-analytical study of proposals, actions and agents that convey ideas about the policy of Merit-based Promotion. In order to do so, we used documental analysis of 67 questionnaires answered by professionals of the educational system of the state of São Paulo (supervisors, directors and teachers) from 04 Boards of Education (from the great ;region of São Paulo and from the countryside of the state), chosen by their profile in the selection process of promotion in 2012. This work, therefore, investigated the policy of Merit-based Promotion, questioning it concerning the ideas, backgrounds, characters, paths, forms and proceedings that form it, focusing them on the perspective of the discourses and actions of the regulators and questioners (context of the influence and the text production), as well as in the perspective of the academic studies (context of the results/effects) and manifestations of educational professionals who work at the public system of the state of São Paulo (context of the practice). Another aim of this investigation was also questioning how the policy strategies are created and recreated, from the regulators and questioners points of view. The main results allowed us to observe, from the analysis of the multiple contexts, how such policy influences careers, practices and conceptions of the professionals of the educational system of the state of São Paulo, acting as a system of control and standardization. It was also possible to confirm the hypothesis that there are many actors who reinterpret and give a new meaning to the policy of Merit-based Promotion; however, the educational professionals are not the most influent actors in this process